Intergovernmental fiscal transfers, forest conservation and climate change - Irawan, Silvia; Tacconi, Luca.; Edward Elgar Publishing ([Cheltenham] : Edward Elgar Pub., 2016)
Intergovernmental fiscal transfers (IFTs) are an innovative way to create incentives for local public actors to support conservation. This book contributes to the debate about how to conserve tropical forests by implementing mechanisms for reducing deforestation and forest degradation (REDD+). With Indonesia as a case study, the authors adopt an interdisciplinary approach, drawing on political science, economics, and public policy. They consider the theoretical justification, as well as the wider political and administrative context for developing the design of IFTs for conservation. Students and scholars looking at conservation, ecological economics, decentralisation, forest policy and climate change will find this book to be of interest. It will also be of considerable use to policy-makers and practitioners working on forest policy, particularly those implementing REDD+. Intergovernmental fiscal transfers (IFTs) are an innovative way to create incentives for local public actors to support conservation. This book contributes to the debate about how to conserve tropical forests by implementing mechanisms for reducing deforestation and forest degradation (REDD+). With Indonesia as a case study, the authors adopt an interdisciplinary approach, drawing on political science, economics, and public policy. They consider the theoretical justification, as well as the wider political and administrative context for developing the design of IFTs for conservation. Students and scholars looking at conservation, ecological economics, decentralisation, forest policy and climate change will find this book to be of interest. It will also be of considerable use to policy-makers and practitioners working on forest policy, particularly those implementing REDD+.
1. Introduction -- 2. Theories of decentralised forest management and fiscal decentralisation -- 3. The cases of Riau and Papua provinces -- 4. Factors affecting local forest governance -- 5. Intergovernmental fiscal transfers and Indonesia's experience -- 6. The design of REDD+ and decentralised forest management -- 7. Incentive structures influencing subnational governments' decisions -- 8. The distribution formulae of IFTs for REDD+ -- 9. Conclusion.
Includes bibliographical references and index.
Description based on online resource; title from title screen (viewed May 20, 2014).
Keywords: Forest conservation; Climatic changes; Conservation of natural resources; Electronic books